Larangan Pernikahan Beda Agama dalam Kompilasi Hukum Islam dan Hak Asasi Manusia - Sawaluddin Siregar; Indra Sakti; Uswatun Hasanah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Marriage is a sacred bond that is carried out by a woman and a man to become husband and wife. Basically every religion has its own proisions regarding marriage. In practice, especially in Indonesia, there are still many who practice interfaith marriages so that this practice has become a discussion that until now and in practice there are also many Muslims who still carry out interfaith marriages. This study aims to examine how the Islamic Law Compilation and Human Rights views the practice of interfaith marriage. The results of this study indicate that both according to the Islamic Law Compilation (KHI) and Human Rights (HAM) state that interfaith marriage is an act that is forbidden because it has violated God’s commands, every religion forbids its people to marry people of different religions. The prohibition on interfaith marriage has also been enshrined in the Marriage Law and also the Islamic Law Compilation, so that every citizen is obliged to follow the applicable legal rules. In human rights, the highest human right is divinity so that every people must obey God’s commands.